ANALYZING RIGHTS OF VICTIMS AN INTERNATIONAL PERSPECTIVE - Shrivastava, Geeta; Tulika; Rani, Mamta (International Journal of Psychosocial Rehabilitation, 2020)
Criminal judicial systems do not grant any rights to the accused or the victim of crime. In all crimes, the accused and his rehabilitation have been given the most attention, but the status of crime victims has been completely overlooked. Justice for offenders is a primary goal of criminal justice, as is ensuring that citizens are protected from abuse. The most essential function of the court is to punish the guilty in line with the law in order to achieve this goal. While convicting the accused, the system has a responsibility to ensure that the accused’s rights are not violated. Following an arrest and conviction, the criminal judicial system is no longer necessary. When a crime is committed, the victim is viewed as the perpetrator’s accuser and as proof. In the eyes of modern victimologists, the notion that victims receive justice simply because the accused has been found guilty is absurd. It’s what they believe, and it’s a governmental duty to safeguard everyone’s life and property from the perpetrators, and the victims are hurting because of that, they say. As a result of the state’s inability to protect crime victims, it owes them an obligation to provide them with restitution.